Women and disasters in South Asia: survival, security and development - Racioppi, Linda, Ed; Rajagopalan, Swarna, Ed (Routledge, 2016)
South Asia is one of the most vulnerable areas of an increasingly disaster-impacted world, with cyclones, earthquakes, floods and droughts causing several casualties and disrupting lives and livelihoods every year. Yet, the impacts of disasters are not equally distributed across the peoples of the region. Women and men experience disaster differently, and their needs in the aftermath of disaster often differ. Bringing together perspectives from academics, emergency responses and development practitioners, the volume investigates to what extent and in what ways gender affects the course of post-disaster reconstruction. Conversely, it also explores in what ways gender politics may be altered by disaster and post-disaster reconstruction. The study includes: a comprehensive overview of key issues facing women and men, as gendered beings, in reconstruction and development; a targeted observation of specific South Asian disaster contexts; and a sustained discussion of case studies and their implications and lessons . This book will interest scholars and researchers of disaster management, rehabilitation studies, gender, environment, ecology, and sociology.